Association between completed suicide and environmental temperature in a Mexican population, using the Knowledge Discovery in Database approach. Issue 135 (October 2016) - Fernández-Arteaga, Verónica; Tovilla-Zárate, Carlos Alfonso; Fresán, Ana; González-Castro, Thelma Beatriz; Juárez-Rojop, Isela E.; López-Narváez, Lilia; Hernández-Díaz, Yazmín
Highlights: We examined the association between environmental temperature and suicide behavior in Mexican population. We used the information of 1357 patients who consummated suicide. We used the Knowledge Discovery in Database with an Apriori algorithm and the data analyses were performed in WEKA software. We observed an association between environmental temperature and suicide. Abstract: Background and objective: Suicide is a worldwide health problem and climatological characteristics have been associated with suicide behavior. However, approaches such as the Knowledge Discovery in Database are not frequently used to search for an association between climatological characteristics and suicide. The aim of the present study was to assess the association between weather data and suicide in a Mexican population. Methods: We used the information of 1357 patients who completed suicide from 2005 to 2012. Alternatively, weather data were provided by the National Water Commission. We used the Knowledge Discovery in Database approach with an Apriori algorithm and the data analyses were performed with the Waikato Environment for Knowledge Analysis software. One hundred rules of association were generated with a confidence of 0.86 and support of 1. Results: We found an association between environmental temperature and suicide: days with no rain and temperatures between 30 °C and 40 °C (86–104 °F) were related to males completing suicide by hanging. Conclusions: In the prevention of suicidal behavior, the Knowledge Discovery in Database could be used to establish climatological characteristics and their association with suicide. This approach must be considered in future prevention strategies.